PERENCANAAN INDOOR BUILDING SOLUTION DI WAHANA TRANS STUDIO BANDUNG - Hasanah Putri (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2020)
The Trans Studio Bandung area is a place to vacation with families that are crowded with visitors. However, there are reports that poor access to cellular services for the operator's LTE network 3. Based on the data from the walktest results around the Trans Studio Building area, bad results are obtained, namely the RSRP value of ? -110 dBm and SINR of ? 6 dB. Based on the survey results, this is due to the thick building material so that the signal does not penetrate well into the room. Based on the identification of OSS data, it shows an imbalance between user traffic and cell capacity that affects network quality and throughput. In this study, the optimization of signal quality using the Indoor Building Solution (IBS) method at a frequency of 1800 MHz, 10 MHz bandwidth, and applying lampsite technology to improve service and capacity in the area. This planning simulation was carried out using IBwave 6.6.4 and the ITU-RP1238 propagation model which is Huawei's standard. Observation parameters in this study are RSRP, SINR, and data rates. The results of the planning show an increase in the average RSRP value of -68.83 dBm, and SINR 22.78 dB. Meanwhile, for data rates, it reached a value of 96.8% for values> = 15 Mbps and the lowest value was 34.82 Mbps. This shows that this plan can provide excellent service to users.